Comparing the normalization of children in traditional and Montessori kindergarten - Mroczkowski, Jamie (My University, 2014)
In this study, the author examined the level of Normalization kindergarten children display in a Montessori classroom and a traditional classroom. Normalization can be demonstrated through the child's love of work, concentration, self-discipline and sociability. Data was gathered from the child and lead teacher through classroom observations, teacher questionnaires, child-interviews and a self-control test. Classroom observations in both environments gave insight into the child's ability to focus and concentrate, as well as observable indications of a love of learning. Teacher questionnaire results were compiled and compared revealing children in Montessori classrooms have more room for choice, multi-sensory material use and more developed literacy skills. The child-interview results indicated that Montessori children were more sociable and self-reliant than traditional school children. Children attending Montessori kindergarten showed a greater level of self-discipline than traditional school children in the self-control test. Ideally, children attending a Montessori children's house should continue their education for kindergarten into their third and final year. The discussion considers the ongoing benefits of staying in a Montessori environment for the kindergarten year.
Plan B Paper. 2014. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 35 leaves. Includes bibliographical references (leaves 34-35).
Keywords: Education, Elementary--Evaluation; Kindergarten--Evaluation; Montessori method of education--Evaluation; Public schools--Evaluation